Fight Identity Theft (FIT) A Comparison of Text-based and Game-based Learning (Journal of The Colloquium for Information Systems Security Education, 2017)
Identity theft is a deceitful method of fraud that negatively affects communities and individuals worldwide. The purpose of this paper is to report results from a study that assessed two educational strategies at the college level that focused on identity theft. One informational delivery method is text-based. The other direction is a game-based method. On examination of the data, results show that students who were exposed to information by way of the game-based method scored higher on the identity theft survey than those who received education through the text-based method. Additionally, the game-based learners continued working in the educational module longer and expressed greater satisfaction with the process than those who were exposed to the text-based informational unit.
Keywords: Crime; Deceit; Deception; Education; Fraud; Fraudster; Identity; Identity Theft; Identity Thieves; Phishing; Scam; Spurious; Theft